Pooling, Separating, and Semiseparating Equilibria in Financial Markets: Some Experimental Evidence - Cadsby, Charles B.; Frank, Murray; Maksimovic, Vojislav (Review of Financial Studies, 1990)
This study investigates experimental financial markets in which firms possess more information than do potential investors. Firms were given opportunities to undertake positive net present value projects which they could either forgo or finance by selling equity. Auctions were conducted among the investors for the right to finance the projects. When the theoretical equilibrium was unique, theory predicted well. When theory permitted pooling, separation, and semiseparation, only the more efficient pooling equilibrium was observed. The domination of the pooling equilibrium was robust to different experimental experiences by participants. When available, signals were used by good firms to distinguish themselves from bad.